'We run for the crumbs and not for office': the Nkrumahist minor parties and party patronage in Ghana. Issue 4 (2nd October 2019) - Bob-Milliar, George M.
ABSTRACT: The staying power of the Nkrumahist minor parties in an institutionalised two-party system is the specific puzzle that underlies this paper. It argues that post-election opportunities for party patronage remain important despite the persistently unsuccessful electoral strategies of the Nkrumahist minor. In national elections minor parties' salience has declined. Nevertheless, the competitiveness of elections sometimes calls for the support of a third-party to win elections. The paper reports that the Nkrumahist parties activated their 'coalition potential' during open presidential races. The few members winning legislative seats used their 'blackmail potential' to gain influence in the government parties. More significant, however, are the post-election patronage opportunities provided by winning parties, involving public sector employment and other forms of recognition.